2000
DOI: 10.1007/pl00011991
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to a new host plant, Centrosema pubescens (Fabales: Leguminosae), by the phytophagous ladybird beetle, Epilachna vigintioctopunctata (Coleoptera: Coccinellidae), in tropical Asia

Abstract: The host suitability of Centrosema pubescens (Leguminosae) was evaluated within two sympatric populations feeding on Solanum plants (Solanaceae) and C. pubescens in Epilachna vigintioctopunctata in Malaysia (Kuala Lumpur) and Indonesia (Bogor and Padang). In the Bogor and Padang populations, Centrosema strains had a significantly higher emergence rate than sympatric Solanum strains. In Kuala Lumpur, there was no significant difference in emergence rates between the two strains. When Centrosema strains from Kua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Finally, the origin of the ability of H. vigintioctopunctata to use centro should also be elucidated in future studies. Until 2013, the utilization of centro by H. vigintioctopunctata has been observed at the southernmost part of Thailand and many parts of Indonesia including northern Sumatra, East Java, Bali, (West, Central, and East) Kalimantan, and South Sulawesi (H. Katakura et al ., unpublished data), as well as at Peninsular Malaysia, West Sumatra, and West and Central Java as reported in the previous studies (Nishida et al ; Shirai & Katakura ; Katakura et al ). On the other hand, H. vigintioctopunctata populations on centro were not found at North Sulawesi (H. Katakura et al ., unpublished data), and at the eastern islands of Indonesia, that is, Lombok, Sumbawa, Flores, and Timor (Fujiyama et al ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Finally, the origin of the ability of H. vigintioctopunctata to use centro should also be elucidated in future studies. Until 2013, the utilization of centro by H. vigintioctopunctata has been observed at the southernmost part of Thailand and many parts of Indonesia including northern Sumatra, East Java, Bali, (West, Central, and East) Kalimantan, and South Sulawesi (H. Katakura et al ., unpublished data), as well as at Peninsular Malaysia, West Sumatra, and West and Central Java as reported in the previous studies (Nishida et al ; Shirai & Katakura ; Katakura et al ). On the other hand, H. vigintioctopunctata populations on centro were not found at North Sulawesi (H. Katakura et al ., unpublished data), and at the eastern islands of Indonesia, that is, Lombok, Sumbawa, Flores, and Timor (Fujiyama et al ).…”
Section: Discussionsupporting
confidence: 80%
“…(formerly referred to as C. pubescens , cf. Fantz ; Schultze‐Kraft ), have been found at West and Central Java, and West Sumatra in Indonesia, and Peninsular Malaysia (Nishida et al ; Shirai & Katakura ; Katakura et al ). Nishida et al () reported that adult beetles collected on solanaceous hosts exclusively preferred S. torvum over centro to feed, whereas those collected on centro showed some degree of acceptance of centro.…”
Section: Introductionmentioning
confidence: 99%
“…(Fabaceae) (Nishida et al . ; Shirai & Katakura ; N. Fujiyama, personal communication). As these adaptive changes occur rapidly in response to changes in the environment (Singer et al .…”
Section: Introductionmentioning
confidence: 98%
“…(Fabaceae) (hereafter referred to as centro) (Nishida et al . 1997; Shirai & Katakura 2000; Katakura et al . 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, at several locations in Southeast Asia, including Java, H. vigintioctopunctata also occurs on an introduced weed Centrosema molle Benth. (Fabaceae) (hereafter referred to as centro) (Nishida et al 1997;Shirai & Katakura 2000;Katakura et al 2001). In a previous study, we had documented the yearly changes in the degree of adaptation to the novel host centro with respect to adult feeding preference and larval developmental performance of a population of H. vigintioctopunctata occurring on both S. torvum and centro at Bogor, West Java (Ueno et al 2017; see also Nishida et al 1997).…”
Section: Introductionmentioning
confidence: 99%